EXPLORING STUDENTS’ EXPERIENCES IN WRITING THESIS PROPOSAL WITH THE ASSISTANCE OF CHATGPT - Triyanti, Erni; Nur, Rafiah; Ammade, Salasiah; Latifa, Ammang; Larekeng, Siti Hajar (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Writing a thesis proposal is an important part of undergraduate education. However, many students face difficulties in writing a thesis proposal, such as selecting an appropriate topic and systematic preparation. In technological developments, ChatGPT can help students in the process of writing a thesis proposal by providing writing assistance, critical thinking, and other information. This research aims to gain the perception and challenges of students in using ChatGPT in assisting them writing their thesis proposals. To get to these aims, the researcher implemented a research and development design by using qualitative methods.. This research was conducted at Al Asyariah Mandar University . The subjects of this research were the seventh semester students of Mathematic Education and Bahasa Indonesia Education in the academic year 2023-2024. In this study, students will be interviewed and asked to share their experiences, the effectiveness and challenges on the assistance of chatgpt in writing their thesis proposals. In the interview results, ChatGPT helps users in finding thesis proposal titles, give information and ideas in building introductions, and providing alternative solutions to deepen the understanding of the proposal. It is important to consider and verify information with more reliable and accurate sources. The use of ChatGPT in writing thesis proposals is an interesting and effective alternative, but users also need to remain critical and selective in utilizing it. In further research, more interviews and case studies need to be conducted to obtain a more comprehensive understanding of the use of ChatGPT in writing thesis proposals. Although ChatGPT has limitations, respondents consider its use to improve productivity and learning efficiency. Therefore, the use of ChatGPT can be considered as an attractive alternative in writing thesis proposals, while maintaining a critical approach in utilizing it and verifying the information provided.